Prevalence of salivary microbial load and lactic acid presence in diabetic and non-diabetic individuals with different dental caries stages - Monika Mohanty; Shashirekha Govind; Shakti Rath (Restorative Dentistry & Endodontics, 2024)
ObjectivesThis study aims to correlate caries-causing microorganism load, lactic acid estimation, and blood groups to high caries risk in diabetic and non-diabetic individuals and low caries risk in healthy individuals.Materials and MethodsThis study includes 30 participants divided into 3 groups: Group A, High-risk caries diabetic individuals; Group B, High-risk caries non-diabetic individuals; and Group C, Low-risk caries individuals. The medical condition, oral hygiene, and caries risk assessment (American Dental Association classification and International Caries Detection and Assessment System scoring) were documented. Each individual’s 3 mL of saliva was analyzed for microbial load and lactic acid as follows: Part I: 2 mL for microbial quantity estimation using nutrient agar and blood agar medium, biochemical investigation, and carbohydrate fermentation tests; Part II: 0.5 mL for lactic acid estimation using spectrophotometric analysis. Among the selected individuals, blood group correlation was assessed. The χ2 test, Kruskal-Wallis test, and post hoc analysis were done using Dunn’s test (p < 0.05).ResultsGroup A had the highest microbial load and lactic acid concentration, followed by Groups B and C. The predominant bacteria were Lactobacilli (63.00 ± 15.49) and Streptococcus mutans (76.00 ± 13.90) in saliva. Blood Group B is prevalent in diabetic and non-diabetic high-risk caries patients but statistically insignificant.ConclusionsDiabetic individuals are more susceptible to dental caries due to high microbial loads and increased lactic acid production. These factors also lower the executing tendency of neutrophils, which accelerates microbial accumulation and increases the risk of caries in diabetic individuals.